2021
DOI: 10.29001/2073-8552-2021-36-3-59-67
|View full text |Cite
|
Sign up to set email alerts
|

The level of reactive oxygen species production by adipocytes of epicardial adipose tissue is associated with an increase in postprandial glycemia in patients with severe coronary atherosclerosis

Abstract: The mechanisms of oxidative stress in adipocytes of local fat depots in patients with cardiometabolic diseases have been studied insufficiently.Purpose. To study the levels of reactive oxygen species (ROS) production in adipocytes of epicardial (EAT) and subcutaneous adipose tissue (SAT) in patients with stable coronary artery disease (CAD) and severe coronary atherosclerosis who underwent coronary artery bypass grafting; to investigate the potential relationships between the levels of ROS production by EAT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Our earlier data evidenced the insulin-mediated dysregulation of EAT adipocytes. The relationships between serum insulin levels (both postprandial and basal) and insulin resistance of EAT adipocytes were demonstrated in patients with coronary heart disease [ 28 ]. In the same study, we demonstrated that insulin resistance of the EAT adipocyte in this category of patients was closely associated with the severity of coronary atherosclerosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our earlier data evidenced the insulin-mediated dysregulation of EAT adipocytes. The relationships between serum insulin levels (both postprandial and basal) and insulin resistance of EAT adipocytes were demonstrated in patients with coronary heart disease [ 28 ]. In the same study, we demonstrated that insulin resistance of the EAT adipocyte in this category of patients was closely associated with the severity of coronary atherosclerosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between serum insulin levels (both postprandial and basal) and insulin resistance of EAT adipocytes were demonstrated in patients with coronary heart disease [ 28 ]. In the same study, we demonstrated that insulin resistance of the EAT adipocyte in this category of patients was closely associated with the severity of coronary atherosclerosis [ 28 ]. These data support the current view that, in contrast to the physiological role of ROS in insulin signaling, ROS overproduction promotes insulin resistance and impairs glucose uptake in adipocytes [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation